Effects of leader material on catches of shallow pelagic longline fisheries in the southwest Indian Ocean - Santos, Miguel (2020)
Catches from a commercial longline fishery targeting swordfish (Xiphias gladius) on monofilament nylon leaders were compared with catches on wire leaders in the Indian Ocean. More taxa were caught on wire leaders, which also showed higher catch rates (13% and 56%, in number and weight, respectively) of blue shark (Prionace glauca). In contrast, catch rates of swordfish were not significantly affected by leader material. Nylon leaders showed lower at-haulback mortality for most bony fishes, except swordfish. Higher bite-off rates were observed on nylon monofilament, likely owing to the escape of species with sharp teeth, such as sharks. Both leader types caught most species within similar size ranges, but larger mean sizes of blue shark were recorded on wire leaders. The value per unit of effort (VPUE) of the retained catch did not differ between leader materials; however, VPUEs are highly dependent on market fluctuations. Banning wire leaders could be an effective way of reducing shark catches, particularly blue shark catches, in the southwest Indian Ocean.